The Role of Government in the Development of the Pampang Cultural Tourism Village - Fauziah, Siti; Lukman, Andi Ismail; Wahyuni, Sri (Journal of Governance and Social Policy, 2024)
The research objectives are: To describe the Government's Role in the Development of Pampang Cultural Tourism Village. In the preparation of this thesis, researchers used a type of qualitative descriptive research with data collection techniques, namely, observation, interviews, and documentation studies. The data source is the government in the pampang cultural village. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results showed that: 1. The facilitator implemented by the government creates conditions conducive to the implementation of cultural management and preservation activities to bridge the various interests of the community and the government in optimizing the program, as a facilitator the government is engaged in assisting training, education, improving skills and funding or capital in the capital program through providing capital assistance to the community, 2. Communicator to maintain good communication between government, community, and artists. Communication is an integral part of a management process through effective communication, harmonious cooperation that can be developed to achieve goals and open cooperation. 3. Catalyst to accelerate the process of an event. To be able to carry out its role as a catalyst, the government also acts as a stimulant to accelerate the process of village potential.